Program “Napas Lega Bersama” untuk Meningkatkan Kualitas Hidup Pasien Penyakit Ginjal Kronik melalui Latihan Pursed-Lip Breathing - Khairunnisa Batubara; Rahmat Ali Putra Harahap; Bitcar Bitcar; Syamsul Idris; Rinawati Rinawati (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Patients with chronic kidney disease (CKD) often experience shortness of breath, fatigue, and a decline in quality of life due to fluid imbalance, anemia, and reduced lung capacity. These conditions highlight the need for simple, safe, and effective non-pharmacological interventions. This community service program, titled “Napas Lega Bersama” (“Breathing Relief Together”), aimed to improve the knowledge and skills of CKD patients in applying pursed-lip breathing (PLB) techniques as a strategy to enhance breathing patterns and overall well-being. The activity was conducted at a partner hospital’s hemodialysis unit through educational sessions, live demonstrations, and guided PLB practice over a two-week period. Pre- and post-program assessments were performed using standardized questionnaires to measure participants’ knowledge and perceived quality of life. The results showed an 85% increase in participants’ understanding of PLB and a 70% improvement in perceived comfort and daily activity performance after the intervention. Participants also reported reduced shortness of breath and greater relaxation during dialysis sessions. This program demonstrates that pursed-lip breathing can serve as a simple and effective complementary therapy to improve the quality of life of CKD patients. It is recommended that this initiative be continued through routine mentoring and interdisciplinary collaboration to promote therapeutic breathing exercises across healthcare settings.